(untitled) (Bangladesh Journal of Medical Microbiology, 2010)
Total 60 mid stream urine samples were collected from suspected urinary tract infection patients of 1 to 12 years age from indoor and outdoor of BSMMU. A total 28 (46.66%) cultures yielded significant growth of single organism & 32 (53.33%) yielded no growth. E. coli was isolated in 53.57% cases, followed by 17.86% Klebsiella spp, 10.71% Enterococcus spp, 7.14% Enterobacter spp, 7.14% Pseudomonas aeruginosa and 3.5% Proteus mirabilis. E. coli was less sensitive to first line drugs including Amoxycillin, Cotrimoxazole, Cephradin, Nalidexic acid ranging (20-27%), but moderately sensitive to Ciprofloxacin (60%), Gentamicin (60%), Ceftriaxone (60%) and highly sensitive to Ceftazidime (80%) and Imipenem (100%). Klebsiella & Enterobacter spp were 100% sensitive to Imipenem and 70% to Amikacin. Enterococci spp shows good sensitivity to Nitrofurantoin (67%), and Imipenem (100%). Pseudomonas spp was highly sensitive to Imipenem and Netilmicin (100%). Bangladesh J Med Microbiol 2010; 03 (02): 18-22